Tenure - Lee, John.; National Education Association, Washington, DC. Higher Education Research Center ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 2001)
Data from the National Study of Postsecondary Faculty (NSOPF:99) show that fewer than one-third of all faculty members were tenured in 1998-1999. Some observers anticipate a trend toward a two-tiered system with a shrinking number of tenured faculty members in one group and a mix of part-time and nontenured full-time faculty members in the other. Analysis of findings from the NSOPF:99 shows that increasing use of part-time faculty, most of whom do not have tenure, is undercutting the tenure system. The evidence for an increasing number of nontenured full-time faculty members is more equivocal. Research also suggests that more faculty members are teaching in institutions that do not offer tenure. Evidence also suggests that faculty members who are not on track for tenure received lower salaries than those on track for tenure. This differential suggests that institutions may use contract or other nontenure track faculty members as lower cost teaching labor. Evidence does not support the charge that tenured faculty members coast on their past achievement, since tenured faculty published more and served on more committees than faculty members without tenure or not on a tenure track. For the most part, the share of women and minority teachers with tenure has increased, closing the gap to some extent. This improvement may represent the efforts to diversify the higher education workforce over the last decade. (Contains 11 figures.) (SLD)
Availability: For full text: http://www.nea.org/he/heupdate/upv1no3.pdf.
ERIC Note: Theme issue.
NEA Higher Education Research Center Update, v7 n3 Jun 2001.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Academic Rank (Professional); College Faculty; Higher Education; National Surveys; Part Time Faculty; Teacher Salaries; Tenure; Trend Analysis; National Study of Postsecondary Faculty; Collected Works, Serials; Numerical/Quantitative Data; Reports, Descriptive